The impact of informal cancer caregiving: A literature review on psychophysiological studies - Teixeira, Ricardo João (2019)
Caregiving can be experienced as a stressful process, which can cause psychological and physical consequences. The combination of prolonged stress and the physical demands of caregiving may impair the physiological functioning of caregivers and increase the risk of health problems creating considerable stress in the life of caregivers regarding emotional, physical, social and financial areas. This literature review explored studies that used measures of the autonomic nervous system in caregivers of oncology patients such as electrodermal and cardiovascular (re)activity. The results revealed that caregivers had elevated stress levels and a serious autonomic imbalance that may, in the long term, trigger negative health consequences such as infectious diseases, cancer progression, cardiovascular disease and even premature death. The results showed the need to carry out preventive strategies in this population, in order to improve the autonomic profile of caregivers of cancer patients.